Data from: Co-inheritance of sea age at maturity and iteroparity in the Atlantic salmon vgll3 genomic region ... - Aykanat, Tutku; Ozerov, Mikhail; Vähä, Juha-Pekka; Orell, Panu; Niemelä, Eero; Erkinaro, Jaakko; Primmer, Craig R (Dryad, 2019)
Co-inheritance in life history traits may result in unpredictable evolutionary trajectories if not accounted for in life-history models. Iteroparity (the reproductive strategy of reproducing more than once) in Atlantic salmon (Salmo salar) is a fitness trait with substantial variation within and among populations. In the Teno River in northern Europe, iteroparous individuals constitute an important component of many populations and have experienced a sharp increase in abundance in the last 20 years, partly overlapping with a general decrease in age structure. The physiological basis of iteroparity bears similarities to that of age at first maturity, another life history trait with substantial fitness effects in salmon. Sea age at maturity in Atlantic salmon is controlled by a major locus around the vgll3 gene, and we used this opportunity demonstrate that these two traits are co-inherited around this genome region. The odds ratio of survival until second reproduction was up to 2.4 (1.8-3.5 90% CI) times ... : Aykanat_et_al_2019_DryadR code and associated objects to replicate main results presented in Aykanat et al, 2019, Co-inheritance of sea age at maturity and iteroparity in the Atlantic salmon vgll3 genomic region, (DOI: 10.1111/jeb.13418) (More details are given in the R code.) ...